Jambi City Government's Strategy for Community Economic Recovery During the Pandemic Through the Pakar Kasih Program - Suhendri; Noor Khalida Magfirah; Saean Hufron (Sospol : Jurnal Sosial Politik, 2023)
Purpose of this study is to determine the Jambi City Government's Economic Recovery Strategy through the Padat Karya Kali Bersih Program (Pakar Kasih) using the Fred R. Dafid concept, namely strategy determination, namely, strategy formulation, strategy implementation, strategy evaluation. Research method used is qualitative with the aim of explaining the phenomenon deeply through data collection by interviewing, observing, and documenting. Results obtained by the Pakar Kasih program are the Jambi Mayor's innovation program in the midst of the Covid-19 pandemic in 2020, which aims to provide a stimulus for people's income to absorb a lot of workers as an additional income for people affected by the economy due to the Covid-19 outbreak. The formulation of the strategy refers to presidential decree number 9 of 2020, government regulations, ministerial regulations of the interior, and Jambi Mayor Regulation Number 37 of 2020. Implementation of the strategy as many as 1102 people of Jambi City participated in the Padat Karya Kali Bersih program at 23 drainage locations in Jambi city. with a length of 25.3 KM with a total APBD of approximately 3 billion. The evaluation of the Pakar Kasih program strategy is held once a year, preferably twice a year or every 6 months.